2021
DOI: 10.1186/s12874-021-01280-3
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the quality of conduct and reporting of survival analyses of tuberculosis outcomes in Africa

Abstract: Background Survival analyses methods (SAMs) are central to analysing time-to-event outcomes. Appropriate application and reporting of such methods are important to ensure correct interpretation of the data. In this study, we systematically review the application and reporting of SAMs in studies of tuberculosis (TB) patients in Africa. It is the first review to assess the application and reporting of SAMs in this context. Methods Systematic review o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 90 publications
(142 reference statements)
1
1
0
Order By: Relevance
“…Younger people had the highest prevalence of anxiety and depression, especially in women, decreasing in older people in all countries, except for men in Peru. These results are consistent with other studies that showed a decrease in the occurrence of mental health problems with increasing age [ 54 ], despite the fact that COVID-19 threatens the physical health of the older population, related to social issues [ 43 ]. In LA, educational centers were closed for an average of more than 1 year, and, despite the boost of virtual classes, this situation increased the effects of the digital divide and emotional apathy [ 20 ].…”
Section: Discussionsupporting
confidence: 93%
“…Younger people had the highest prevalence of anxiety and depression, especially in women, decreasing in older people in all countries, except for men in Peru. These results are consistent with other studies that showed a decrease in the occurrence of mental health problems with increasing age [ 54 ], despite the fact that COVID-19 threatens the physical health of the older population, related to social issues [ 43 ]. In LA, educational centers were closed for an average of more than 1 year, and, despite the boost of virtual classes, this situation increased the effects of the digital divide and emotional apathy [ 20 ].…”
Section: Discussionsupporting
confidence: 93%
“…In a review of papers published in the cancer literature in an earlier period and whose findings may not pertain to current statistical practice, Altman et al 2 found that only 5% of papers assessed whether the assumptions of the Cox model were satisfied. Ngari et al 3 examined the quality of survival analyses in studies of tuberculosis outcomes published between 2010 and 2020. Of the 67 studies that reported using a Cox proportional hazards model, 32 (48%) stated that the proportional hazards assumption had been tested, while only 2 (3%) reported the results of such a test.…”
Section: Introductionmentioning
confidence: 99%